(untitled) (Economia Aplicada, 2018)
This paper studies the effects of fiscal news on the Brazilian economy, building on the new literature that seeks to identify fiscal policy shocks through information from professional forecasts. I build a term structureof primary balance expectations in Brazil, and estimate fiscal reaction functions for different maturities. Primary balance forecasts are decomposed into an expected and unexpected component, based on predicted and residuals obtained from the reaction functions. Expected and unexpected fiscal news are identified respectively as the first factor of the predicted and residual series from the reaction functions, aiming to capture the news that are likely to persist over the forecast horizon. Although with substantial uncertainty, fiscal tightening news induce a short-lived increase in growth, fall in inflation, decline in the real wage and a depreciation of the real exchange rate.